(untitled) (International Journal of Banking and Finance, 2025)
Digital financial inclusion is a fundamental component in alleviating poverty and enhancing prosperity. A comprehensive financial system lays the foundation for a basis of robust and resilient households, enhancing the welfare of low-income groups. This research examines the determinants of digital financial inclusion among low-income families in Malaysia, specifically focusing on digital literacy, financial literacy, trust, infrastructure and financial service providers. Total of one thousand one hundred seventy-one respondents with income below the national poverty line were surveyed. The Partial Least Squares-Structural Equation Modelling (PLS-SEM) and the Multigroup Analysis (MGA) techniques were employed. This study separated the total sample into two groups, Peninsular Malaysia and East Malaysia. The results demonstrate that trust, digital literacy and infrastructure are positively and significantly related to digital financial inclusion for all the groups. The role of financial service providers is only supported for the complete sample set and Peninsular Malaysia. Surprisingly, this study found no association between financial literacy and digital financial inclusion. In addition, the MGA results further evidence significant differences between Peninsular Malaysia and East Malaysia in achieving digital financial inclusion. Peninsular Malaysia shows stronger digital literacy and infrastructure, while East Malaysia demonstrates more potents effects of financial service providers and trust in boosting digital financial inclusion. These findings provide practitioners valuable insights into fostering a digitally inclusive financial society. This research includes strengthening consumer protection regulations on digital financial services to address cyber threats, implementing digital literacy campaigns to enhance awareness, and ensuring affordable and reliable internet access. These policy recommendations highlight the importance of formulating and designing tailored strategies to enhance digital financial inclusion among low-income households in Malaysia.